2016
DOI: 10.5414/cn108633
|View full text |Cite
|
Sign up to set email alerts
|

Organism-specific bacteremia by hemodialysis access

Abstract: The frequency and type of positive blood culture in HD patients are highly associated with type of access used. The high rate of CNS bacteremia with CVC in conjunction with low ESI rate suggests that contamination at the time of accessing the catheter may be the problem. Staff training was followed by a decrease in infection rates. Trending organism-specific bacteremia infection rates in HD units may provide important clues to bacteremia causality and thus prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…These rates are similar to a Japanese Society for Peritoneal Dialysis report covering 3042 patients, and 114 centers over 31,686 patient months that reported a rate of 0.195 episodes per years, with a very low rate of Staphylococcus epidermidis of 0.01 episodes per year at risk (31). In reality, patients who start dialysis using a hemodialysis catheter are at high risk for positive blood cultures, many fold higher than performing dialysis using an arteriovenous fistula (32). This is probably in part why mortality is higher in those starting dialysis with a hemodialysis catheter than those starting dialysis with a PD catheter or with an arteriovenous fistula or graft (33).…”
Section: Risk Of Peritonitissupporting
confidence: 79%
“…These rates are similar to a Japanese Society for Peritoneal Dialysis report covering 3042 patients, and 114 centers over 31,686 patient months that reported a rate of 0.195 episodes per years, with a very low rate of Staphylococcus epidermidis of 0.01 episodes per year at risk (31). In reality, patients who start dialysis using a hemodialysis catheter are at high risk for positive blood cultures, many fold higher than performing dialysis using an arteriovenous fistula (32). This is probably in part why mortality is higher in those starting dialysis with a hemodialysis catheter than those starting dialysis with a PD catheter or with an arteriovenous fistula or graft (33).…”
Section: Risk Of Peritonitissupporting
confidence: 79%
“…However, the rate is still higher than in general population. 29 , 33 Patients with MRSA bacteremia had higher mortality compared with those with MSSA bacteremia. 34 Despite the use of appropriate antibiotic, a significantly high mortality was found in the MRSA compared with MSSA infections.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis catheter uses were at higher risk of bacteremia compared with arteriovenous fistula or graft uses. A single center study in the United States indicated that the rate of positive blood cultures in patients with central venous catheters was 1.86/1000 d and 0.08/1000 d in patients with an arteriovenous fistula and 0.31/1000 d in patients with an arteriovenous graft[30]. Rate of infection related hospitalization was higher in the patients with catheters or arteriovenous grafts compared with arteriovenous fistula, the rate ratios were 1.59 and 1.37, respectively[5].…”
Section: Risk Factorsmentioning
confidence: 99%